AB0864 Extensive evaluation of biomarkers related with bone turnover in patients with ankylosing spondylitis. (23rd January 2014) - Taylan, A.; Sari, I.; Akinci, B.; Bilge, S.; Kozaci, D.L.; Akar, S.; Yalcin, H.; Gunay, N.; Akkoc, N.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease of spine and sacroiliac joints and characterized by new bone formation. Osteoporosis is also accompanied with AS.Human nuclear factor κβ ligand (RANKL) stimulate osteoclasts. Osteoprotegrin (OPG), which is produced by osteoblasts, inhibits RANKL and plays an important role in bone formation. The Wnt signaling cascade and the secreted inhibitor of Wnts, Sclerostin, Dickkopfs (Dkks) and secreted frizzled related proteins (sFRP1) play important roles in bone turnover Objectives: We investigated changes in bone mineral density (BMD) and the levels of various biomarkers related with bone turnover with regard to clinical parameters, disease activity and treatment regimen with/without anti TNFα drugs. Methods: Fifty five AS patients (48Males) and 33 controls (24Males) were included in the study. Spinal mobility was assessed by the Bath Ankylosing Spondylitis Metrology Index (BASMI) and radiologic changes were scored by bath ankylosing spondylitis radiologic index (BASRI). Patients were also evaluated with the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI).BMD of hip and spine and various bone turnover biomarkers were measured. Results: Conclusions: OPG was lower and correlated with active disease state in AS patients. Wnt signal pathway inhibitors level did not altered in AS and ongoing ectopic bone formation may be related dysfunction of these molecules at cellular level.There is a complex interaction of anti TNF α drug with various cytokines. OPG is decreased but Dkk1 is increased on anti TNF α treatment in AS patients. Even clues of the osteoblastic effects of anti TNF α treatment, concrete role of these drugs both on osteoporosis and ectopic bone formation still need to be clarified. Disclosure of Interest: None Declared